PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada Kantor Telkom Divre IV di Semarang) - Pane, Jagarin; Astuti, Sih Darmi (Jurnal Ilmiah Telaah Manajemen, 2009)
This research propose to examine the effect organization culture, tranformational leadership, and compensation, on employee performance. Ninety eight respondents from PT Telkom Region IV Semarang, completed 65 items self-reported measures. The data collected survey method and questionares distributed to respondent. The statistic method used was Multiple Regression. As expected, result indicated that tranformational leadership and compensation has a positive effects on employee performance, while organization culture didn’t have effect on employee performance, it’s mean that ‘the telkom way 135’ which made since 2003 couldn’temployee perform, because before it telkom had strong organization culture. Furthermore, results show that tranformational leadership have a stronger effect on employee performance than compensation.Keywords: Organization Culture, Transformational Leadership, Compensation, and Employee Performance